Karakterisasi Bakteri Termofilik Penghasil Enzim Protease Netral - Widia Firliani; Anthoni Agustien; Fuji Astuti Febria (Universitas Andalas, 2015)
A study on the characterization of thermophilic bacteria in producing neutral protease enzyme has been conducted in the Laboratory of Microbiology, Biology Department, Andalas University from October 2013 to March 2014. The bacteria were isolated from a hot spring at Sungai Medang, Kerinci. Water samples were collected purposively based on gradient temperature at the hot spring which ranged from 450C to 880C. Colony of the bacteria were inoculated using nutrient agar (NA). We obtained 10 isolates of neutral protease enzyme from the thermophilic bacteria with proteolytic index ranged from 0.27 to 3.89. The MIV-14 isolate has the highest proteolytic index which collected from 830C of the hot spring. Characterization of macroscopic, microscopic and biochemical tests were reported. Generally, the colonies have round shape, wavy edge, white, producing endospores and motile. Keywords: characterization, neutral protease, thermophilic bacteria.